Penyusunan dan Penerapan Peraturan Desa tentang Pengendalian Schistosomiasis di Daerah Endemis - Junus Widjaja; Ahmad Erlan; Intan Tolistiawaty; Yuyun Srikandi; Hasrida Mustafa (Jurnal Vektor Penyakit, 2021)
ABSTRACT In Indonesia, schistosomiasis is caused by the blood worm Schistosoma japonicum, resulting harmful impact on the economy and public health. Can lead to including stunting (stunting) and reduced learning ability, especially in of children. Schistosomiasis elimination strategies include cross-sectoral involvement and community participation. Implementation of the Bada Model is community empowerment in an effort to control schistosomiasis. Implementation of the Schistosomiasis Village Regulation is an important part. Methods were activities of drafting, submitting the drafts to the secretariat of the Poso Regional Government, socializing village regulations and ratifying village regulations and evaluating the implementation of village regulations. There was a decrease in the prevalence of schistosomiasis in humans, increased fecal collection coverage, and a decline in the number of snail foci. The application of village regulations apparently strengthens the control of schistosomiasis in endemic areas. ABSTRAK Di Indonesia, schistosomiasis disebabkan oleh cacing darah Schistosoma japonicum, Dampak buruk pada ekonomi dan kesehatan masyarakat. stunting dan berkurangnya kemampuan belajar pada anak-anak. Strategi eliminasi schistosomiasis antara lain keterlibatan lintas sektor dan peran serta masyarakat, Implementasi Model Bada merupakan pemberdayaan masyarakat dalam upaya pengendalian schistosomiasis, Pelaksanaan Peraturan Desa Schistosomiasis merupakan salah bagian yang penting. Metode melalui pembuatan draf, pengajuan draf ke sekretariat Pemda Poso, sosialisasi perdes, pengesahan perdes dan evaluasi penerapan perdes. Adanya penurunan prevalensi schistosomiasis pada manusia, peningkatan cakupan pengumpulan tinja dan berkurangnya jumlah fokus keong. Penerapan Perdes menguatkan pengendalian schistosomiasis di daerah endemis.